Capitalism, imperialism and European Union Law: towards a Marxist approach - Robert Knox; Eva Nanopoulos; Andrew Woodhouse (European Law Open)
This article establishes a foundation for the development of Marxist approaches to European Union (EU) law. While Marxist scholarship has engaged with European integration throughout its history, it has largely overlooked the legal architecture of the EU. Conversely, EU legal studies have remained largely insulated from Marxist thought, even as critical approaches have begun to gain traction. Bridging this mutual neglect, the article argues that EU law must be understood not as a neutral or technocratic system, but as a central element of capitalist social relations both in Europe, and in terms of Europe’s wider integration in the global market. In this way, EU law is bound up with processes of accumulation, imperialism, and racialised social reproduction. Drawing on key currents within Marxist theory, the article situates EU law within the historical dynamics of capitalist development, demonstrating how a materialist legal analysis can deepen and enrich existing critiques of European integration.